THE POSITIVE EFFECT OF WORKING DURING UNIVERSITY STUDIES - Nilufar Mamajonova; Zohidbek Norboyev; Dostonjon Ravshanov; Asilbek Abdurakhmonov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article explores the positive impacts of working while attending university, focusing on skill development, financial independence, time management, and enhanced employability. Through literature analysis and survey-based research, it examines how work experience influences academic and career outcomes. Findings reveal that working during university can foster essential skills and career advantages, though balance is key. The article concludes with recommendations for students, universities, and employers on maximizing the benefits of student work experience.